The effect of school construction on test scores, school enrollment, and home prices - Christopher Neilson; Seth Zimmerman (Institute for the Study of Labor (IZA), 2011)
This paper provides new evidence on the effect of school construction projects on home prices, academic achievement, and public school enrollment. Taking advantage of the staggered implementation of a comprehensive school construction project in a poor urban district, we find that, by six years after building occupancy, 10,000 of per-student investment in school construction raised reading scores for elementary and middle school students by 0.027 standard deviations. For a student receiving the average treatment intensity this corresponds to a 0.21 standard deviation increase. School construction also raised home prices and public school enrollment in zoned neighborhoods.
urn:nbn:de:101:1-201111213488
Keywords: I21; I22; H75; R30; 330; school construction; test scores; home prices; Schule; Öffentlicher Bau; Nachbarschaft; Schulbesuch; Bildungsniveau; Wohnung; Immobilienpreis; Schätzung; USA